PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI UPT PUSKESMAS KARANGANYAR KABUPATEN LEBAK (Fakultas Ekonomi dan Bisnis Universitas Faletehan, 2022)
In this study, the following conclusions can be drawn, the average respondent's response to the competence variable is high, where the average score of respondents' answers is 3.822 on a scale of 3.41-4.20, respondents' responses to the performance variable are high , where the average score of respondents' answers is 3.850 on a scale of 3.41-4.20, respondents' responses to the performance variable are high, where the average score of respondents' answers is 3.850 is at 3.41-4.20 scale. The test results found that competence had no significant effect on employee performance at UPT Puskesmas Karanganyar, Lebak Regency. The test found that work discipline had a significant and positive effect on employee performance at UPT Puskesmas Karanganyar, Lebak Regency. While the test results showed that competence and work discipline together affect the performance of employees at UPT Puskesmas Karanganyar, Lebak Regency.